Epidermal NBN deletion causes premature hair loss and a phenotype resembling psoriasiform dermatitis - Seidel, Philipp; Remus, Martina; Delacher, Michael; Grigaravicius, Paulius; Reuss, David; Frappart, Lucien; Deimling, Andreas von; Feuerer, Markus; Abdollahi, Amir; Frappart, Pierre-Olivier (OncoTarget, 2016)
Nijmegen Breakage Syndrome is a disease caused by NBN mutations. Here, we report a novel function of Nbn in skin homeostasis.
Gesehen am 27.05.2020